An Overview on India Electricity Market (London Journal of Research In Management & Business, 2024)
Indias electricity generation started based on technologies available in XIX century on coal. Strating with XX century oil and natural gases were introduced as new sources for energy production being mainly used for transport and industry. Like in other countries the energy sector was heavily regulated and under state control until last decade of XX th century. The actors of the market like electricity production plan, transmission and distribution networks, gas, oil and coal extraction industry were mainly state -owned. Strating with 1991 Indian federal government launch important reforms on economic sector in order to increase the importance of market economy, these reforms affecting also the energy sector. The Electricity Law issued in 1991 and lately amended was the first step for cease state monopoly on power generation allowing also the other companies state or private to step into this sector and to start generation without special license. Still at that time the state maintains its monopoly on transmission and distribution networks. The reforms continued and new Electricity Act adopted in 2003 enlarge the energy sector reforms allowing private investments also in transport and distribution networks having the final scope a better protection of the clients through competition. Present century due the global commitment of reducing GHG and CO2 emission determinate India to follow the general orientation through renewable energies.
Keywords: Institutional Evaluation. Strategic Anticipation. Higher Education; Civilisations; performance; nepotism; sociometry; culture.; ocial media; Photo posting; Social commerce; Training; effectiveness; communication; experiential learning; Continuous Improvement